APPLICATION OF ONLINE DISPUTE RESOLUTION (ODR) IN INTERNATIONAL AND INDONESIA DOMAIN NAMES DISPUTES - Dheka Ermelia Putri (Faculty of Law Universitas Lampung, 2019)
The Online Dispute Resolution has become a breakthrough in the world of law, especially the law of dispute settlement. Online Dispute Resolution is used in several disputes such as e-commerce disputes and domain name. Technically, part of the ODR has been used by Indonesia’s Constitutional Court, where the Indonesian Constitutional Court utilizes video conferencing facilities in listening to witness testimonies and expert opinions. Moreover, PANDI (Pengelola Nama Domain Indonesia) has implemented most of the functions of the ODR in resolving Domain Name disputes in Indonesia like one of the cases that has been resolved, we call as “Netflix.id” Case that is the case of the Netflix Company who has used Netflix’s name as merchandise since 1977. Netflix Company knowing that there is a new domain name that uses the name of the item, namely “Netflix.id” is officially registered and this interferes with the trading of the Netflix Company, with the result that Netflix Company filed a lawsuit to namely removing the “Netflix.id” domain name. This case was resolved without going through a face to face PPND Process (Pedoman Perselisihan Nama Domain) as a legal basis under Indonesian legislation Currently. Online Dispute Resolution has been used by various world organizations including UNCITRAL, European Commission, and WIPO Arbitration and Mediation. PANDI (Pengelola Nama Domain Internet Indonesia) as one of the parties that utilize the online dispute resolution has policies established under existing international regulations. Still, the ODR has been applied in some cases and resulted in binding decisions to the parties.